Persepsi Remaja terhadap Konten Hadiah Mesin Capit pada Akun TikTok Willie Salim - Sabrina Dhiya Apryani; Mareta Puri Rahastine; Anggie Ayu Astria Latuperissa (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
This study examines late adolescents’ perceptions of claw-machine gift content uploaded on Willie Salim’s TikTok account, a form of viral content that presents gift-giving activities through an interactive game concept. Based on Jalaluddin Rakhmat’s perception theory, this study analyzes three stages of perception: attention, interpretation, and evaluation, to understand how young audiences perceive and interpret digital sharing content. A qualitative case study approach was applied involving five late-adolescent informants aged 17–19 years residing in RT 003 RW 015, Puri Cendana Housing Complex, Tambun, selected through purposive sampling. Data were collected through non-participant observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing, supported by methodological triangulation. The results indicate that adolescents’ attention is influenced by internal factors, such as familiarity and experience, as well as external factors, including visual attractiveness, prize value, and content presentation. Informants generally interpreted the content as a combination of sharing and entertainment, although some questioned the creator’s underlying motives. The evaluation stage showed predominantly positive and neutral perceptions, with critical awareness of possible content construction. The study concludes that entertainment value and perceived sincerity significantly shape adolescent perceptions of digital sharing content.